Boshlangʻich sinflarda oʻqish savodxonligi darslarida oʻquvchilarning insoniy fazilatlar ruhida tarbiyalash - Qosimova Mehriniso ilhomovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article examines the importance and methods of educating students in the spirit of human qualities in reading literacy classes in creative classrooms. The article emphasizes the importance of observing such qualities as goodness, kindness, honesty, and conscientiousness in children for personal development of students and for them to become useful members of society. The article shows the possibility of using such methods as marking texts, holding discussions, role playing, social life and personal example in teaching literacy lessons. In the article, the article emphasizes that the process of teaching human skills should be long and continuous, and that teachers can contribute to the spirit of human skills of children related to parents.